Analyzing the Treatment of Patients with Acute Exacerbation of COPD with the Aid of Intelligent Diagnosis Method. (12th March 2022) - Jiang, Qina; Zhao, Guangxiang; Song, Shiyan; Chen, Yujuan
Abstract : To observe the clinical efficacy of heat clearing phlegm mixture combined with vibration sputum excretion instrument in the treatment of patients with acute exacerbation of COPD with phlegm-heat obstructing lung, 90 patients with acute exacerbation of COPD are selected and divided into three groups, namely, control group, traditional medicine group, and combined group: the control group (conventional western medicine treatment), traditional medicine group (heat clearing and phlegm mixture), and combined group (heat clearing and phlegm mixture + vibratory sputum excretion instrument) with 30 cases each. All the patients in the three groups were given conventional western medicine treatment. On this basis, the traditional medicine group was given the oral administration of the heat-clearing and phlegm-clearing mixture, and the combined group was given the oral administration of the heat-clearing and phlegm-clearing mixture and the vibratory sputum discharge apparatus. Machine learning is used to classify the patients into three groups based on the characteristics of their biomarkers, physical attributes, and medical history. The TCM syndrome score, blood gas analysis, lung function, and inflammatory indexes of the three groups were compared. TCM syndrome scores of the three groups were all lower than before; both the combined group and the TCM group were better than the control group (P  < 0.05). Although the improvement degree of the combined group was better than that of the TCM group, the difference was not statistically significant (P  > 0.05). TCM syndrome effect is seen to be 96.55% in the combined group, 89.29% in the TCM group, and 63.33% in the control group. Blood gas analysis is also performed; PO2 and PCO2 of the three groups were significantly improved after treatment. The combination group was superior to the traditional medicine group and the control group (P  < 0.05), and the traditional medicine group was superior to the control group (P  < 0.05). It is concluded that the combination of heat clearing phlegm mixture and vibration sputum excretion instrument can improve TCM syndrome score, CAT score, blood gas analysis, lung function, and inflammatory indicators in patients with acute exacerbation of COPD with phlegm-heat obstructing lung.